“Los títeres en el desarrollo emocional de los niños y niñas del primer grado de Educación Básica paralelo “A” de la Unidad Educativa “Riobamba” de la ciudad de Riobamba, período lectivo 2015 – 2016”. - Lema Quillupangui, María Cristina (2017)
The research was designed to determine the importance of puppets in the emotional development of boys and girls of the first grade of Basic Education, parallel “A” of “Riobamba” Educational Unit, from Riobamba city, school period 2015 – 2016. This process begins with the referential framework starting from the problem statement and formulation, questions guidelines, objectives, justification importance. The theoretical foundation refers to the contents related to the independent variable that corresponds to emotional development. Concerning the methodological framework, the inductive and deductive method start with the experimental research design, type of research is descriptive, explanatory, field, bibliographical and the level of research is diagnostic and experimental. The population is 34 boys and girls of first grade of basic; observation was used as a technique and the instrument is the observation sheet and the conclusions and recommendations are given. Research work aims to help boys and girls to improve their emotional development using the puppets as teaching instrument so that in the future children can develop freely without shyness and gain self – confidence.